Effects of Controlled Irrigation and Drainage on Nitrogen and Phosphorus Concentrations in Paddy Water - Shi-kai Gao; Shuang-en Yu; Guang-cheng Shao; Dong-li She; Mei Wang; Rong Guo; Rui-zhe Cao; Shao-feng Yan; Ji-hui Ding (Journal of Chemistry)
Controlled irrigation and drainage (CID) has received attention for improving water quality. Under CID condition, water stress is frequently experienced in two contexts: first drought and then flooding (FDTF) and first flooding and then drought (FFTD). This study aimed to investigate the effects of FDTF and FFTD on nitrogen (N) and phosphorus (P) dynamics in paddy water at different growth stages. The effects of water stress on the migration and transformation of N and P were also investigated. Results showed that CID can decrease N and P concentrations in surface water. NH4+-N was the major form of N in surface drainage and percolation water. Mean total phosphorus (TP), NH4+-N, and NO3--N concentrations were significantly higher than in FFTD during the growth stage. Mean NH4+-N, NO3--N, and TP concentrations were significantly higher in percolation water under flooding stress than those under drought stress at growth stage, except for mean TP concentrations at milky stage (stage IV). Meanwhile, flooding can sharply increase the NH4+-N, NO3--N, and TP concentrations in percolation water after drought. Thus, without CID, the considerably high NH4+-N, NO3--N, and TP concentrations via runoff and leaching can be responsible for the eutrophication of water bodies in the vicinity of paddy fields during the rice growing season when water stress transforms from drought into flooding.